2022
DOI: 10.1007/s00402-022-04687-9
|View full text |Cite
|
Sign up to set email alerts
|

Long-term results after anterior cruciate ligament reconstruction using patellar tendon versus hamstring tendon autograft with a minimum follow-up of 10 years—a systematic review

Abstract: Introduction A lot of research addresses superiority of the two commonly used autografts bone-patellar tendon-bone (BPTB) and hamstring tendon for anterior cruciate ligament (ACL) reconstruction, without getting to consensus. While there are numerous studies and reviews on short- to mid-term follow-up, not much literature is available on long-term follow-up. As patients suffering ACL injuries are often of young age and high athletic activity, it is crucial to have the best evidence possible for g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
1
3
0
Order By: Relevance
“…However, it is crucial to consider that the studies included in that review are dated to the 1990s and the current standard of practice could be more accurate in terms of tunnel preparation and femoral tunnel placement. However, these data were similar to those reported by Sollberger et al [ 21 ]. In their systematic review, they reported a rate of knee OA ≥ 2 (KL classification) in 32–55.2% of cases after 10 years of follow-up.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, it is crucial to consider that the studies included in that review are dated to the 1990s and the current standard of practice could be more accurate in terms of tunnel preparation and femoral tunnel placement. However, these data were similar to those reported by Sollberger et al [ 21 ]. In their systematic review, they reported a rate of knee OA ≥ 2 (KL classification) in 32–55.2% of cases after 10 years of follow-up.…”
Section: Discussionsupporting
confidence: 93%
“…However, the mean follow-up period was 82 (minimum 48 and maximum 108) months. A recent systematic review and meta-analysis that compares the clinical results between HT and patellar tendon reported a failure rate of HT graft from 6.3% to 18% at minimum 10 years of follow-up [ 21 ]. Our results showed a lower rate of graft failure (5.4%) compared to existing literature [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of the 2598 studies initially identified from the search strategy, a total of 50 systematic reviews (36 systematic reviews with meta‐analyses, 14 systematic reviews alone) were included in the final quality assessment (Figure 1) [1‐7, 10‐13, 16, 19, 21‐23, 25‐29, 31‐33, 35, 38‐42, 44, 46, 48, 52, 54, 58‐60, 65‐69, 71‐75, 77]. Cohen's κ Scores were 0.73, 0.75 and 0.74 at the title/abstract, full‐text screening and AMSTAR‐2 assessment stages, respectively, indicating substantial agreement at all phases of the review.…”
Section: Resultsmentioning
confidence: 99%
“…Hamstring tendon autografts are widely used for anterior cruciate ligament (ACL) reconstruction [ 1 ]. However, slower graft-tunnel incorporation, graft maturation, and tunnel widening remain some of the biggest concerns with hamstring autografts compared with BTB autografts [ 2 4 ]. Several studies have investigated different methods for enhancing graft-tunnel healing to increase osteointegration, including the use of bone morphogenic proteins, platelet-derived growth factors, transforming growth factor-b1 (TGF-b1), bone substitutes, and periosteum autografts [ 5 7 ].…”
Section: Introductionmentioning
confidence: 99%